China moves the G20 on international investment - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Under China's leadership, the G20 adopted "Guiding Principles for Global Investment Policymaking," put investment facilitation on the international agenda and institutionalized an additional platform for investment discussions. The challenge is now to build on these accomplishments.
Keywords: 330